Calculation of Current Distribution Inside the Metallized Film Capacitor Element at High Frequency - Yi, Chengqian; Zhang, Bo; Li, Chaoran; Li, Qi; Hu, Jun; He, Jinliang (IEEE transactions on dielectrics and electrical insulation, 2025)
Metallized film capacitors (MFC) for converter valves are subject to high-frequency current shocks during power electronic switching, which will lead to uneven current distribution inside capacitor elements, thus affecting the stability and reliability of the entire capacitor. In this article, to solve the problems of complex structure, complicated electromagnetic coupling, and large calculation scale due to a large number of ultrathin layers when calculating the current distribution based on the finite element method (FEM), the method of equivalent simplification of complex structure and the method of taking values of equivalent parameters were proposed. Then the calculation model of current distribution inside a capacitor element was established. Using the model, the impedance characteristics, the magnetic field distribution, and the current distribution of two types of capacitor elements, symmetric and asymmetric, were calculated. The agreement of the calculated results with those from the literature and measurements proved the correctness of the calculations. The results show that the current distribution inside a capacitor element is highly dependent on the external connection leads, and the current distribution is not uniform at high frequencies. This calculation model of current distribution inside the capacitor element can support the study of the performance evolution, fault analysis, and optimization design of MFC.